Recapturing the Value Through Reverse Logistics Practices: A Review - Bokade, Sanjay; Raut, D. N. (Prabandhan: Indian Journal of Management, 2011)
Reverse Logistics has become an area of key competence in modern supply chains - Products, components; materials and other equipment stream forward and backwards and back in their supply chains. Reverse Logistics deals with the processes associated with the reverse stream from users/owners to re-users. More precisely, reverse logistics is the process of moving goods from their typical final destination for the purpose of capturing value, or proper disposal. This paper provides a review and content analysis of scientific literature on reverse logistics to develop a strategic framework to improve practices of Reverse Logistics. Further, criticality of Reverse Logistics in comparison to Forward logistics has been elaborated. Various reasons of returns and need of reverse logistics have been investigated. Forecasting, Planning and handling of such returns had been explored. Further, two case studies of corporates using good Reverse Logistics practices are mentioned. The paper explores the various areas of research in this field. The paper emphasizes on the need as well as opportunities of Reverse Logistics. It is further concluded with the need of a strategic framework by the enterprises to handle their returns and recapture the value.